Immediate reduction in left ventricular ejection time following TAVI is associated with improved quality of life - Schenk, Jimmy; Kho, Eline; Rellum, Santino; Kromhout, Joris; Vlaar, Alexander P. J.; Baan, Jan; van Mourik, Martijn S.; Jorstad, Harald T.; van der Ster, Björn J. P.; Westerhof, Berend E.; Bruns, Steffen; Immink, Rogier V.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background TAVI has shown to result in immediate and sustained hemodynamic alterations and improvement in health-related quality of life (HRQoL), but previous studies have been suboptimal to predict who might benefit from TAVI. The relationship between immediate hemodynamic changes and outcome has not been studied before. This study sought to assess whether an immediate hemodynamic change, reflecting myocardial contractile reserve, following TAVI is associated with improved HRQoL. Furthermore, it assessed whether pre-procedural cardiac power index (CPI) and left ventricular ejection fraction (LVEF) could predict these changes. Methods During the TAVI procedure, blood pressure and systemic hemodynamics were prospectively collected with a Nexfin® non-invasive monitor. HRQoL was evaluated pre-procedurally and 12 weeks after the procedure, using the EQ-5D-5L classification tool. Results Overall, 97/114 (85%) of the included patients were eligible for analyses. Systolic, diastolic and mean arterial pressure, heart rate, and stroke volume increased immediately after TAVI (all p<0.005), and left ventricular ejection time (LVET) immediately decreased with 10ms (95%CI= -4 – -16, p<0.001). Overall HRQoLindex increased from 0.810 [0.662 - 0.914] before to 0.887 [0.718 - 0.953] after TAVI (p=0.016). An immediate decrease in LVET was associated with an increase in HRQoLindex (0.02 index points per 10ms LVET decrease, p=0.041). Pre-procedural CPI and LVEF did not predict hemodynamic changes or change in HRQoL. Conclusion TAVI resulted in an immediate hemodynamic response and increase in HRQoL. Immediate reduction in LVET, suggesting unloading of the ventricle, was associated with an increase in HRQoL, but neither pre-procedural CPI nor LVEF predicted these changes.